A sugar–lectin rich interface between soft tissue and the stiff byssus of Atrina pectinata. (9th June 2020) - Choi, Jimin; Hennebert, Elise; Flammang, Patrick; Hwang, Dong Soo
Abstract : Various types of carbohydrates and lectins were found at the mechanically mismatched interface of byssus of Atrina using histochemistry and proteomics. Abstract : Maintaining durable adhesion between soft tissues and relatively hard implant materials is one of the most elusive technological difficulties in bionic devices due to contact damage between mechanically mismatched materials. Although there are many examples of coexistence of soft and hard tissues in living organisms, relatively little is known about the mechanisms used to overcome mechanical mismatches occurring at the interface between soft and hard tissues. Among the various creatures possessing mechanically mismatched biological tissues, Atrina pectinata is a good model system where the interface between stiff byssal threads and soft tissues is distributed all over an extended organ. In this study, we found a wide distribution of various types of carbohydrates and lectins at the mechanically mismatched interface of the byssus of Atrina using histological methods and proteomics. Reversible and robust interactions between the carbohydrate and lectins at the interface would play a major role in mitigating the contact damage at the Atrina interface. Based on these results, the adhesion between sugar and lectin would be useful to overcome a wide range of contact damage observed in research studies on bionic devices.